The Influence of Interlocking Directorates on the Propensity of Dividend Payout to the Parent Company. (27th May 2020) - Siudak, Dariusz
Abstract : An examination was performed on whether director interlocks enabled the adoption of a dividend policy for the benefit of the parent company in the ownership structure. Specifically, the study investigated the dependence of the impact of the central position in the board network on the probability of dividend payment. Based on sample of firms listed on Polish capital market, it was observed that the more central the company's position in the interlocking directorate network, the more likely it is to pay dividends to a subsidiary. This effect is related to the eigenvector centrality. The results obtained suggest that corporate financial policy can be spread across firms through the board network.